Hair cell-type dependent expression of basolateral ion channels shapes response dynamics in the frog utricle - Venturino, Alessandro; Oda, Adriano; Perin, Paola (Frontiers in Cellular Neuroscience, 2015)
The dynamics of vestibular afferent responses are thought to be strongly influenced by presynaptic properties. In this paper, by performing whole-cell perforated-patch experiments in the frog utricle, we characterized voltage-dependent currents and voltage responses to current steps and 0.3-100 Hz sinusoids. Current expression and voltage responses are strongly related to hair cell type. In particular, voltage responses of extrastriolar type eB (low pass, -3 dB corner at 52.512.8 Hz) and striolar type F cells (resonant, tuned at 6046 Hz) agree with the dynamics (tonic and phasic, respectively) of the afferent fibers they contact. On the other hand, hair cell release (measured with single-sine membrane Cm measurements) was linearly related to Ca in both cell types, and therefore did not appear to contribute to dynamics differences. As a tool for quantifying the relative contribution of basolateral currents and other presynaptic factors to afferent dynamics, the recorded current, voltage and release data were used to build a NEURON model of the average extrastriolar type eB and striolar type F hair cell. The model contained all recorded conductances, a basic mechanosensitive hair bundle and a ribbon synapse sustained by stochastic voltage-dependent Ca channels, and could reproduce the recorded hair cell voltage responses. Simulated release obtained from eB-type and F-type models display significant differences in dynamics, supporting the idea that basolateral currents are able to contribute to afferent dynamics; however, release in type eB and F cell models does not reproduce tonic and phasic dynamics, mainly because of an excessive phase lag present in both cell types. This suggests the presence in vestibular hair cells of an additional, phase-advancing mechanism, in cascade with voltage modulation.